Benjamin fra Tudela. Rejsedagbogen i dansk oversættelse II - Kupczyk Lewin, Lola (Nordisk judaistik/Scandinavian Jewish Studies, 1994)
A translation of the travel diaries of the medieval Jewish traveler Benjamin of Tudela.